Invasive Nontyphoidal Salmonella Infection in a Patient with Early-Stage Chronic Lymphocytic Leukemia - Deepika Slawek; Yanina Dubrovskaya; Eddie Louie (Case Reports in Infectious Diseases)
We describe a case of a 72-year-old man with early-stage chronic lymphocytic leukemia (CLL) who presented with invasive nontyphoidal Salmonella (iNTS) infection, necrotizing pneumonia, and chronic infection of a hilar lymph node. Infection is a major cause of death in patients with CLL. Though few cases of iNTS infection associated with CLL have been described in the literature, to our knowledge this is the first reported case of iNTS-associated necrotizing pneumonia. Immunocompromised state in patients, even with early-stage CLL, likely predisposes them to invasive infection with intracellular organisms, such as Salmonella spp. In this case, successful treatment was achieved with prolonged course of intravenous followed by oral antibiotics without any surgical removal of infected focus.